2008
DOI: 10.4049/jimmunol.180.10.6703
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Proximal Signaling Events after TCR/CD8-Mediated Induction of Proliferation or Apoptosis in Mature CD8+ T Cells

Abstract: Engagement of the TCR can induce different functional outcomes such as activation, proliferation, survival, or apoptosis. How the TCR-mediated signaling cascades generating these distinct cellular responses are organized on the molecular level is so far not completely understood. To obtain insight into this question, we analyzed TCR/CD8-mediated signaling events in mature OT-I TCR transgenic T cells under conditions of stimulation that lead to either proliferation or apoptosis. These experiments revealed major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…Indeed, we and others have demonstrated that OT-I transgenic T cells and cytotoxic T-lymphocyte clones are not activated and do not differentiate upon stimulation with antibodies cross-linked in suspension (Berg et al, 1998;Wang et al, 2008). Here, we have stimulated primary human T cells with either sAbs or iAbs and analyzed their functional responses.…”
Section: Iabs Induce Activation and Proliferation Whereas Sabs Resumentioning
confidence: 83%
See 1 more Smart Citation
“…Indeed, we and others have demonstrated that OT-I transgenic T cells and cytotoxic T-lymphocyte clones are not activated and do not differentiate upon stimulation with antibodies cross-linked in suspension (Berg et al, 1998;Wang et al, 2008). Here, we have stimulated primary human T cells with either sAbs or iAbs and analyzed their functional responses.…”
Section: Iabs Induce Activation and Proliferation Whereas Sabs Resumentioning
confidence: 83%
“…For more than 30 years, this method has been extensively employed and indeed, has provided significant insight into the molecular events occurring during T-cell activation. However, stimulations with soluble ligands have clear limitations, as they fail to reproduce the extra dimension of a cell-cell contact and, more importantly, they do not induce T-cell responses (Berg et al, 1998;Wang et al, 2008). Thus, it is questionable whether TCR signaling induced upon stimulation with soluble Abs mirrors the physiologic signaling cascade leading to productive T-cell responses.…”
Section: Introductionmentioning
confidence: 97%
“…Using OT-1 TCR Tg preselection CD4 + CD8 + thymocytes and specific peptides spanning the boundary of positive and negative selection, it was found that negatively selecting peptides recruited Ras, Raf-1, and RasGRP1 to the PM, whereas these molecules colocalized to internal cellular sites, perhaps the Golgi and/or other endomembranes, when thymocytes were stimulated with a peptide mediating positive selection (56). In addition, studies on peripheral OT-1 CD8 T cells correlated active ERK being localized to the PM when cells were induced to undergo apoptosis, whereas a condition promoting survival and proliferation was associated with ERK activation present at endosomal compartments (57). The rationale for alternate cellular sites of Ras activity may be to subject it to differential regulation and/or serve to pair it with a unique subset of effectors.…”
Section: Discussionmentioning
confidence: 99%
“…Although CD8αα and CD8αβ bind similarly to MHC class I molecules (8), CD8β endows CD8 with coreceptor functions. Indeed, CD8αβ, but not CD8αα, associates with TCR/ CD3, strengthens pMHC binding (3-5, 9, 10), and promotes CD8 association with lipid rafts and p56 lck (lymphocyte-specific tyrosine kinase, lck) and hence TCR signaling via lck-mediated phosphorylation of CD3 ITAMs, followed by recruitment and activation of Zeta-chain-associated protein kinase 70 (ZAP-70), phosphorylation of Linker for activation of T cells (LAT), and diverse downstream signaling cascades, including activation of phospholipase C-γ (PLCγ), mobilization of intracellular Ca 2+ , and translocation of the transcription factor, Nuclear factor of activated T cells (NFAT) (3)(4)(5)(9)(10)(11). CD8β-KO mice have two-to-threefold lower numbers of CD8 + T cells, showing that CD8β plays an important but not essential role in the thymic selection of CD8 + T cells (5,12,13).…”
mentioning
confidence: 99%